Using the GPR Method to Detect Weak Zones in the Soil underneath the Foundation of the Ghaidan Building, Karbala City, Iraq - Mohammed, Ammar J. (Iraqi Journal of Science, 2025)
The study area holds great importance as it is situated in the historically significant region of Karbala, one of the most religious centers in the entire Islamic world. The Al-Hussein and Al-Abbas holy shrines are religious and archaeological sites, for more than 600 years ago. Karbala has more importance for all Islamic peoples because it is the place of Al-Imam Al-Hussein and his brother Al-Abbas holy shrines and martyr graves of Al-Hussein family and friends whom they had martyred beside him in Al-Tuff battle in the year 61 hijri. The word Karbala means soft earth, but historically, it meant life and safety. According to old Iraqi language the name of Karbala was country of safety. Ghaidan building is located at the center of Karbala about 100 km south of Baghdad. It is a modern building that was built in 2020 on soil containing the ruins of an old building. The area of the building is 71 m2 and its dimensions are 6.20m ×11.45m. A differential settlement of the soil occurred due to the dewatering process for a nearby building, which led to the withdrawal of fine soil particles and consequently the occurrence of cavities, and then differential settlement, which led to its inclination towards the southeast. The main purpose of conducting a Ground Penetrating Radar survey is to identify areas of weakness in the soil underneath the foundation of the building. The presence of cavities and weak zones in the soil underneath the foundation caused a movement of the building structure towards the southeastern side, which represents the front part of the building. It is indicated that the soil underneath the foundation down to 5.5 m is relatively loose (i.e., not compacted), which causes differential settlement and affects, to a large extent, the building structures.